Pengantar Editor-in-Chief Mediapsi Volume 6 Nomor 2 Tahun 2020 - Mashuri, Ali (MEDIAPSI, 2020)
In this introduction, the editor-in-chief briefly described the topic of seven empirical articles that have been published in Mediapsi volume 6 number 2, 2020. Broadly speaking, the topics of the articles in this edition varied, from those of clinical psychology to educational psychology, and social psychology. The first article examined the role body dissatisfaction had in explaining subjective well-being, especially among women in emerging adulthood. The topic of the second article pertained to various aspects of the classroom atmosphere and their impacts on elementary school studentsâ€™ subjective well-being. Shifting the topic from elementary school students to high school students, the third article was a correlational study examining how much peer conformity and emotional intelligence predicted career adaptability. The fourth article was an experimental study, which investigated the effect of a socialisation program on the propensity of healthy behaviours among caregivers of cancer patients, followed by the fifth article zooming on in the relationship between critical thinking and religious tolerance among high school students. The sixth article was about how regional students construed the meanings of home, which was analysed qualitatively. The last, seventh article examined the levels of outgroup prejudice based on two factors, that is, intergroup contact and demographic variables (i.e., gender, age, education).Dalam pengantar ini, editor-in-chief memberikan gambaran ringkas atau kesimpulan mengenai topik tujuh artikel empiris yang telah dimuat di Mediapsi volume 6 nomor 2 tahun 2020. Secara garis besar, topik artikel dalam edisi tersebut cukup bervariasi, mulai dari psikologi klinis, psikologi pendidikan, sampai dengan psikologi sosial. Artikel pertama meneliti topik tentang peran body dissatisfaction terhadap subjective well-being, khususnya pada perempuan yang memasuki masa emerging adulthood. Topik kedua menelaah sejauh mana ragam aspek suasana kelas menjadi prediktor subjective well-being pada anak-anak sekolah dasar. Bergeser dari anak sekolah dasar ke remaja sekolah menengah atas, artikel ketiga merupakan studi korelasional untuk menguji peran konformitas dengan teman sebaya dan kecerdasan emosi dalam menjelaskan adaptabilitas karier. Artikel keempat adalah studi eksperimen, yang menginvestigasi pengaruh penyuluhan untuk meningkatkan kecenderungan perilaku sehat caregiver pasien kanker, diikuti dengan artikel kelima tentang hubungan antara berpikir kritis dan toleransi beragama di kalangan siswa sekolah menengah atas. Artikel keenam tentangÂ pemaknaan rumah pada mahasiswa rantau yang menganalisis topik ini secara kualitatif. Artikel ketujuh sekaligus terakhir meneliti tinggi rendahnya prasangka terhadap kelompok lain atas dasar dua faktor, yaitu kontak antarkelompok dan variabel-variabel demografis (jenis kelamin, usia, dan tigkat pendidikan).Â